Using a Relative Quantitative Proteomic Method to Identify Differentially Abundant Proteins in Brucella melitensis Biovar 3 and Brucella melitensis M5-90 - Zhang, Huan; Wang, Yueli; Wang, Yifan; Deng, Xiaoyu; Ji, Taiwang; Ma, Zhongchen; Yang, Ningning; Xu, Mingguo; Li, Honghuan; Yi, Jihai; Wang, Yong; Wang, Yuanzhi; et al. (Frontiers in Immunology, 2022)
Brucellosis, caused by Brucella spp., is one of the most widespread bacterial zoonoses worldwide. Vaccination is still considered the best way to control brucellosis. However, many hurdles remain regarding the present Brucella vaccine. An investigation into the differential proteome expression patterns of two different Brucella strains may help researchers and clinicians differentiate between the strains to diagnose and better understand the mechanism(s) underlying differences in virulence. In the present study, a mass spectrometry-based, label-free relative quantitative proteomics approach was used to investigate the proteins expressed by the wild strain, B. melitensis biovar 3 and compare it with those expressed by B. melitensis M5-90. The higher level of virulence for B. melitensis biovar 3 compared to B. melitensis M5-90 was validated in vitro and in vivo. A total of 2133 proteins, encompassing 68% of the theoretical proteome, were identified and quantified by proteomic analysis, resulting in broad coverage of the B. melitensis proteome. A total of 147 proteins were identified as differentially expressed (DE) between these two strains. In addition, 9 proteins and 30 proteins were identified as unique to B. melitensis M5-90 and B. melitensis biovar 3, respectively. Pathway analysis revealed that the majority of the DE proteins were involved in iron uptake, quorum sensing, pyrimidine metabolism, glycine betaine biosynthetic and metabolic processes, thiamine-containing compound metabolism and ABC transporters. Furthermore, the specific metabolic pathways involved in iron uptake, ABC transporters, quorum sensing and thiamine-containing compound metabolism were associated with Brucella virulence, survival and drug resistance. The expression of BtpA and VjbR proteins (two well-known virulence factors) in B. melitensis biovar 3 was 8-fold higher than that in B. melitensis M5-90. In summary, our results identified many unique proteins that could be selected as candidate markers for differentiating vaccinated animals from animals with wild-type infections. BtpA and VjbR proteins might be responsible for the residual virulence of B. melitensis M5-90, while ABC transporters and thiamine metabolism associated proteins may be newly identified Brucella virulence factors. All of the identified DE proteins provide valuable information for the development of vaccines and the discovery of novel therapeutic targets.